Mối liên hệ của lòng tự trọng và sự tự giám sát bản thân đối với sự tự bộc lộ bản thân chân thực trên tài khoản Facebook riêng tư của sinh viên Đại học Quốc gia Thành phố Hồ Chí Minh - Nguyễn, Thảo Phương; Nguyễn Thùy Nhung; Nguyễn, Thị Minh Thư; Võ, Thị Thúy Nhân (Tạp chí Giáo dục, 2025)
Social networking sites have become popular platforms for social communication and interaction and have become a topic that has received much attention from researchers. A new behavior on these platforms is the creation of multiple accounts by multiple users to easily manage and control the information they disclose online, but this behavior has not been studied in detail. The study applied a quantitative method with a sample of 333 university students in Ho Chi Minh City to investigate the relationship between self-monitoring, self-esteem, and self-disclosure on private accounts when using Facebook among university students aged 19 to 22. The results showed that self-monitoring and self-esteem can predict the level of authentic self-disclosure on private Facebook accounts. These findings contribute to the understanding of how users present themselves on social media and suggest that individuals with higher levels of self-monitoring and self-esteem tend to share more authentic information in private online environments.